Menelaah Amanat Agung Tuhan Yesus Menurut Matius 28:19-20 Bagi Pemberita Kabar Baik - Sine, Hendricks; Nainggolan, Alon Mandimpu (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2023)
This study uses biblical studies and descriptive qualitative methods to describe the meaning of the Great Commission of the Lord Jesus based on Matthew 28:19-20. Through this research, it was found that in Matthew 28:19-20 there are four important points: clear authority or authority, clear goals, clear task details, and guarantees for God's inclusion. Integrating the divine and the human element in preaching the gospel is significant. Understanding and applying various contextual strategies as a manifestation of the human element can increase success in preaching the gospel, whether through centripetal or centrifugal missions. Being a disciple of Christ means being faithful to involve yourself as well as possible and full of responsibility in carrying out the Great Commission of the Lord Jesus. The mission of evangelism and discipleship today is not only the task of pastors, missionaries or evangelists, church councils, or servants of God. However, it is the duty of every believer. God enables every believer to carry out this glorious calling with perfect inclusion.